2022
DOI: 10.1177/10547738221112748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Covid-19 Pandemic on the Prevalence of Insomnia, Anxiety, and Depression During Pregnancy: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis study aims to determine the effects of the Covid-19 pandemic on the prevalence of insomnia, anxiety, and depression symptoms during pregnancy. Reviews were done through PubMed, EBSCO (Medline, CINAHL), Embase (OVID), Web of Science, PsycINFO, TR Index, Turkish Thesis Center databases using (pregnancy OR pregnant) and (sleep OR sleep disorders OR insomnia), and (anxiety OR depression) keywords between April and May 2021. The meta-analysis included 48 articles (sample: 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
(273 reference statements)
0
4
0
Order By: Relevance
“…For the umbrella review, we identified 904 systematic reviews with or without meta-analyses. Of those, 781 reviews were excluded for several reasons such as not including a meta-analysis or wrong outcome ( Fig 1 ), retaining 123 eligible reviews with meta-analyses of primary studies published in 2021 and 2022 (initial search [ 9 , 10 , 25 80 ]; updated search [ 5 , 81 144 ]).…”
Section: Resultsmentioning
confidence: 99%
“…For the umbrella review, we identified 904 systematic reviews with or without meta-analyses. Of those, 781 reviews were excluded for several reasons such as not including a meta-analysis or wrong outcome ( Fig 1 ), retaining 123 eligible reviews with meta-analyses of primary studies published in 2021 and 2022 (initial search [ 9 , 10 , 25 80 ]; updated search [ 5 , 81 144 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety, depression, and stress symptoms are highly prevalent in pregnant women [ 6 , 33 ]. These psychological factors can alter maternal mental health, which can dramatically affect the child development [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, because most of these studies were retrospectively evaluated, it is difficult to say that only the pandemic influenced this process. Pregnancy itself carries the risk of anxiety and depression in women (14)(15)(16)(17)(18)(19)(20). In our study, it was found that the anxiety scores of normal pregnant women were higher than those of high-risk pregnant women.…”
Section: Discussionmentioning
confidence: 46%